PERAN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA ANAK USIA DINI - Fitriani, Laily; Harjanty, Rokyal (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was a qualitative descriptive study. Types of data in this research was in the form of primary data and secondary data. Then the data collection techniques used are observation, interviews and documentation which aims to find out: 1). How positive thinking therapy can increase the self-confidence of Karate martial arts athletes at SMA 1 Praya Timur, 2). What is the process of implementation and the results of positive thinking therapy for karate martial arts at SMA 1 Praya Timur. The subjects of this study were SMA 1 Praya Timur martial arts athletes, who had been selected according to specific characteristics according to the research objectives. In accordance with the results of the discussion, the researchers showed that: 1) the self-confidence of SMA 1 Praya Timur Karate martial arts athletes, what needs to be increased is 10 athletes, 2). The process of implementing and the results of positive thinking therapy went well and the results of positive thinking therapy can be used to increase the confidence of martial arts athletes, only 1 athlete experienced less change after positive thinking therapy was carried out so that follow-up was needed for the athlete's treatment.